GPs views and understanding of PSA testing, screening and early detection; survey. Issue 5 (May 2016) - Sutton, J.; Melia, J.; Kirby, M.; Graffy, J.; Moss, S.
Summary: Background: There is currently no national prostate cancer screening programme in the UK. However, patients 50 years and older are entitled to a prostate specific antigen (PSA) test, if informed on the advantages and disadvantages of testing and their risk of cancer. The Prostate Cancer Risk Management Programme (PCRMP) provides this guidance. Aim: The aim of this study was to access GPs' views and understanding of PSA testing, prostate cancer screening and early detection. Method: A total of 708 questionnaires were returned by GPs across two English regions in 2013 and the GP questionnaire responses were quantitatively analysed. Results: In the 699 completed questionnaires, the majority of GPs were well informed about PSA testing, screening and early detection. Only 32% used guidelines for referral, 14% knew all age‐specific PSA referral levels, 71% that Black men have a higher prostate cancer risk than White men (22% correctly answered threefold increase) and 82% that family history is a risk factor. A further 78% thought electronic prompts during consultation would encourage PCRMP guideline usage and 75% had never been offered a PSA test and prostate cancer educational course, of which 73% would like to attend a course. Only 23% were aware of the latest PSA screening evidence1 and 94% would like an update. Conclusions: Participating GPs seem to be well informed but need more information and tools to help follow recommended guidance. In particular, increased awareness of PCRMP guidelines especially by automated methods, further educational courses and evidence updates would be beneficial.